ISGylation is increased in the peripheral blood mononuclear cells derived from symptomatic COVID-19 patients. Issue 10 (May 2022) - Schwartzenburg, Joshua; Reed, Ryan; Koul, Hari; Zea, Arnold H; Shellito, Judd; Miele, Lucio; Crabtree, Judy S; Desai, Shyamal
Cytokine-driven hyper inflammation has been identified as a critical factor behind poor outcomes in patients severely infected with SARS-CoV-2 virus. Notably, protein ISGylation, a protein conjugated form of Type 1 IFN-inducible ubiquitin-like protein ISG15 (I nterferon-S timulatedG ene15 ), induces cytokine storm (CS) and augments colonic inflammation in colitis-associated colon cancers in mouse models. However, whether ISGylation is increased and causally responsible for CS and hyper inflammation in symptomatic COVID-19 patients is unknown. Here, we measured ISGylation levels in peripheral blood mononuclear cells (PBMCs) from 10 symptomatic (SARS-CoV-2-positive with symptoms) and asymptomatic (SARS-CoV-2-positive with no symptoms) COVID-19 patients, and 4 uninfected individuals (SARS-CoV-2-negative), using Wes Tm assay. Strikingly, we note significant increases in protein ISGylation and MX-1 (myxovirus-resistance protein-1) protein levels, both induced by type-I IFN, in symptomatic but not in asymptomatic patients and uninfected individuals. Knowing that ISGylation augments CS and intestinal inflammation in colon cancers, we propose that increased ISGylation may be an underlying cause of CS and inflammation in symptomatic patients.